Initial experience using the Penumbra coil 400: comparison of aneurysm packing, cost effectiveness, and coil efficiency. (15th March 2013) - Milburn, James; Pansara, Ankit Limba; Vidal, Gabriel; Martinez, Raisa Coral
Abstract : Background/objective: This was a retrospective single operator experience of aneurysm coiling at the Ochsner Clinic, comparing the Penumbra coil 400 with the other most commonly used coil types, Orbit and Galaxy. Methods: 40 aneurysms treated exclusively with Orbit or Galaxy coils and 18 aneurysms treated only with Penumbra coils from 2010 to February 2012 were compared. Measurements included packing density, number of coils per unit aneurysm volume, and total coil length per unit aneurysm volume. Results: Mean packing density of 33.7% using Penumbra coils was significantly greater than 24.4% for Orbit/Galaxy coils. The number of coils per aneurysm volume of 0.026 coils/mm 3 for the Penumbra coil was significantly lower than 0.114 coils/mm 3 for the Orbit/Galaxy coils. Aneurysm occlusion rates were similar in both groups. Conclusions: Compared with the Orbit/Galaxy coils, our analysis suggests that the Penumbra coil is more efficient and cost effective in the treatment of intracranial aneurysms.